2014
DOI: 10.1007/s12020-014-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between TNM staging system and histopathological features in patients with papillary thyroid carcinoma

Abstract: We aimed to assess the validity of the American Joint Committee on Cancer (AJCC) tumor-node-metastasis (TNM) staging system in patients with papillary thyroid carcinoma (PTC) by evaluating the relationships between clinicopathologic factors and TNM stage using histopathological specimens and electronic medical records. We enrolled 733 consecutive patients who had undergone thyroid surgery for PTC between 2010 and 2013. Clinical data were obtained from electronic medical records. TNM stages, multifocality, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In contrast, in our study, occult contralateral papillary carcinoma was significantly more frequent in patients with a tumor [0.5 cm according to postoperative pathology, which is consistent with the results of Lee et al [9]. In addition, Ryu et al [26] reported that PTC primary tumor size was significantly associated with T and N stages in the AJCC TNM staging system, which are independent predictors of multifocality and bilaterality. It has also been reported that patients with a tumor size[1 cm are more likely to have tumor recurrence in a regional lymph node [27].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, in our study, occult contralateral papillary carcinoma was significantly more frequent in patients with a tumor [0.5 cm according to postoperative pathology, which is consistent with the results of Lee et al [9]. In addition, Ryu et al [26] reported that PTC primary tumor size was significantly associated with T and N stages in the AJCC TNM staging system, which are independent predictors of multifocality and bilaterality. It has also been reported that patients with a tumor size[1 cm are more likely to have tumor recurrence in a regional lymph node [27].…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between tumor size and aggressive histological features was also analyzed. Multifocality, ETE, bilaterality, vascular invasion, lymph node metastases and distant metastases were compared in eight (1214,18,19,24,25,28), five (14,18,19,22,27), three (12,18,28), four (7,12,13,18), eleven (6,7,12,14,1820,24,2830) and five (7,12,14,18,24) studies, respectively. Based on the meta-analysis, S2 was found to be associated with aggressive histological features more often compared with S1 , including ETE (OR=2.575, 95% CI=1.603–4.135; P <0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been indicated that tumor size is correlated with lymph node metastasis, extrathyroidal extension, recurrence, and poor overall survival. [8][9][10][11][12] Tumor size is also a risk factor in the American Joint Committee on Cancer TNM system. The small sample size was the primary reason for the marginal correlation seen in this study.…”
Section: Discussionmentioning
confidence: 99%